Commitment and Coordination: Studies on the Implementation of Poverty Alleviation Policies in Makasar City - Hasniati; Ibrahim, Muhammad Akmal; Lambali, Suryadi; Anirwan; Zainal, Nining Haslinda; Fatimah, Siti (Journal of Local Government Issues, 2023)
Makasar City is one of the cities with the highest poverty problem in South Sulawesi so that poverty alleviation policies are carried out. This study aims to identify and analyze commitment and coordination in the implementation of the Poverty Reduction Program (PAP) in Makassar City. The research method uses a qualitative approach with in-depth interviews and document reviews. This paper will answer two questions: How is the government's commitment to PAP? How is the coordination between agencies in the distribution of PAP? The results of the study show that the commitment of the government of Makassar City is relatively high. But unfortunately, the commitment of government elites has not been fully supported by the commitment of implementers at the RT/RW level. The pattern of coordination between organizations has not gone well, and this is indicated by differences in data between Regional Work Unit (SKPD) in terms of the number of poor people.